Analysis Of Peer Group Support and the Learning Environment with Learning Motivation for Nursing Students - Monica Novyanti Surbakti; Agustaria Ginting; Ance M Siallagan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Learning motivation is a driving force from within a person to carry out activities including learning in achieving achievement. Motivation to learn can be seen from the results of exams and even from everyday phenomena such as studying only during exams, being sleepy while studying, working together during exams. If that motivation is not increased and instilled in oneself, it can lead to a degradation of enthusiasm, it can even lead to a loss of enthusiasm for learning. The purpose of this study was to analyze the relationship between peer group support and the learning environment with the learning motivation nursing students. The research design used correlation with cross sectional approach. The population and research sample were 93 people using total sampling technique. Data collection is done directly using a questionnaire. Based on the results of the study, the average peer group support is found to be 60.67, standard deviation 6.611, min-max value 37-77, estimate interval 59.31-62.03. Learning environment with a mean of 42.04, standard deviation of 4.147, min-max value of 31-35, estimates interval of 41.18-42.90. Motivation to learn with an average of 67.55, standard deviation 6.470, min-max value 52-80, estimates interval 66.22-68.88. The results of the Pearson product moment statistical test between peer group support and a learning environment with learning motivation found p-values ??of 0.001 and 0.007, respectively. The correlation value of peer group support and learning environment with positive learning motivation is 0.346 and 0.279, respectively. This means that there is a significant relationship between peer group support and the learning environment with learning motivation and the higher the value of the peer group and learning environment, the greater the score of learning motivation. It is hoped that STIKes Santa Elisabeth Medan will continue to improve peer groups and comfortable infrastructure, away from noise in increasing student motivation to learn.